THE CLUSTER ANALYSIS APPROACH FOR CLASSIFICATION OF ANDHRA PRADESH ON THE BASIS OF RAINFALL (MAUSAM, 1994)
The ave rage linkllBe method of cluster analys is was appl ied (or classifying the di stricts of AndhraPrad esh on th e b asis of monthly rainfall recorded. in diff ere nt sea so ns . The meth od of cluste ring h as the ad va nta geof least subjectivity in clu ster formati on unlike th at of the pri nci pa l components method. Th e a nalysis was ca rriedou t seasonwise on th e basis of 30 )~ ars of monthly rain fa ll data covering th e yea rs 1961-62 to 1~91. [I was foundthat the di stri cts ofAndh ra Prad esh ca n be classified iuto 5 10 7 d usters which depend on the seaso n. Ea st and WeslGod avari districts of coastal Andh ra region exh ib ited a similar pat tern in the rainfall of all the seasons: cert ain d istricts c f Telangan a region also exh ibi ted a simila r pan crn in rai nfall of all th e seasons excepting the 5Ou th~SI mensoon.In ce rtai n clu eters . there was 8 representetien u t'Ji.oJlril,,·u from all th e three ~ii ons of the Stale, Seesonwiseclust erings a re also di scu ssed .